PKD1 mutation may epistatically ameliorate nephronophthisis progression in patients with NPHP1 deletion. Issue 2 (9th January 2019) - Watanabe, Saki; Ino, Jun; Fujimaru, Takuya; Taneda, Sekiko; Akihisa, Taro; Makabe, Shiho; Kataoka, Hiroshi; Mori, Takayasu; Sohara, Eisei; Uchida, Shinichi; Nitta, Kosaku; Mochizuki, Toshio
Key Clinical Message: We report a patient with adult‐onset nephronophthisis (NPHP) that was identified a homozygous full gene deletion of NPHP1 and a heterozygous PKD1 mutation. We suggest that the PKD1 mutation may have epistatically ameliorated NPHP disease progression and that the screening of larger cohorts for similar possible epistatic effects is needed. Abstract : We report a patient with adult‐onset nephronophthisis (NPHP) that was identified a homozygous full gene deletion of NPHP1 and a heterozygous PKD1 mutation. We suggest that the PKD1 mutation may have epistatically ameliorated NPHP disease progression and that the screening of larger cohorts for similar possible epistatic effects is needed.